Molecular Characterization of Two Fatty Acyl-CoA Reductase Genes From Phenacoccus solenopsis (Hemiptera: Pseudococcidae). Issue 1 (7th June 2016) - Li, Xiaolong; Zheng, Tianxiang; Zheng, Xiaowen; Han, Na; Chen, Xuexin; Zhang, Dayu
Abstract: Fatty acyl-CoA reductases (FARs) are key enzymes involved in fatty alcohol synthesis. Here, we cloned and characterized full-length cDNAs of two FAR genes from the cotton mealybug, Phenacoccus solenopsis. The results showed PsFAR I and PsFAR II cDNAs were 1, 584 bp and 1, 515 bp in length respectively. Both PsFAR I and PsFAR II were predicted to be located in the endoplasmic reticulum by Euk-mPLoc 2.0 approach. Both of them had a Rossmann folding region and a FAR_C region. Two conservative motifs were discovered in Rossmann folding region by sequence alignment including a NADPH combining motif, TGXXGG, and an active site motif, YXXXK. A phylogenetic tree made using MEGA 6.06 indicated that PsFAR I and PsFAR II were placed in two different branches. Gene expression analysis performed at different developmental stages showed that the expression of PsFar I is significantly higher than that of PsFar II in first and second instar nymphs and in male adults. Spirotetramat treatment at 125 mg/liter significantly increased the expression of PsFar I in third instar nymphs, but there was no effect in the expression of PsFar II . Our results indicated these two FAR genes showed different expression patterns during insect development and after pesticide treatment, suggesting they play different roles in insect development and detoxification against pesticides.